Analisis Pengaruh Keputusan Berobat Dalam Memediasi Kunjungan Pasien: Studi SEM Analisis - Meutia Arifka Tahajani Husen; Andry Andry; Reza Hilmy (Jurnal Health Sains, 2022)
The decision to choose a hospital as a place for treatment is something that can affect patient visits because the decision to seek treatment is able to mediate the positive influence of motivation, consumer interest, perceived quality and brand image on patient visits. This study aims to analyze the effect of motivation, consumer interest, perceived quality and brand image on patient visits with treatment decisions as an intervening variable at Hospital A. This study uses explanatory quantitative analysis of causality with the SEM Analysis method. This study took a sample of 165 visitors ( patients) By using a random sampling technique. The independent variables in this study are motivation, consumer interest, perceived quality and brand image and the dependent variable is patient visits and treatment decisions as intermediary variables. This study shows that there are direct and indirect impacts between motivation, consumer interest, perceived quality and brand image. on patient visits with treatment decisions as an intervening variable at Hospital A. Improving the marketing system of the hospital and improving the health care system so that it can affect motivation, patient interest, perception of quality and brand image in deciding to seek treatment at Hospital A which has a positive influence on increasing patient visits